Suppression of chronic damage in renal allografts by liver X receptor (LXR) activation: relevant contribution of macrophage LXRα - Kiss, Eva; Popovic, Zoran V.; Bedke, Jens; Wang, Shijun; Bonrouhi, Mahnaz; Gretz, Norbert; Stettner, Paula; Teupser, Daniel; Thiery, Joachim; Porubský, Štefan; Adams, Judith; Gröne, Hermann-Josef (The American journal of pathology, 2011)
Liver X receptors (LXR)-α,β regulate intracellular cholesterol homeostasis and inhibit inflammatory gene expression. We studied the effects of the LXRα,β-agonist GW3965 on acute and chronic organ damage in the F344-LEW rat kidney transplantation model. In addition, to gain LXR isoform and cell-specific insights BALB/c kidneys were transplanted into mice with macrophage overexpression of LXRα (mLXRα-tg) and evaluated 7 and 42 days after transplantation. After 56 days GW3965 improved significantly function and morphology of rat kidney allografts by substantial reduction of mononuclear cell infiltrate and fibrosis; in vitro GW3965 reduced inflammatory activity of bone marrow-derived macrophages (BMDMs) and alloreactivity of T cells. Kidneys transplanted into mLXRα-tg mice were also protected from development of chronic allograft dysfunction. Similarly to GW3965-activated BMDMs, mLXRα-tg macrophages secreted significantly less monocyte chemoattractant protein 1 and macrophage inflammatory protein 1β. Interestingly, 7 days after transplantation, when the total number of intragraft macrophages did not differ, evidently more arginase 1- and mannose receptor C type 1-positive cells were found in LXR rat and mice kidney allografts; in vitro both LXR activation by GW3965 and mLXRα overexpression accentuated the induction of alternative activation of BMDMs by IL-4/IL-13, suggesting an additional mechanism by LXRs to prevent graft damage. The results highlight the relevance of macrophage LXRα in allograft rejection and prevention of fibrosis.
Gesehen am 04.08.2022